2010
DOI: 10.1080/14786410902904376
|View full text |Cite
|
Sign up to set email alerts
|

GC-MS analysis of the leaf surface components of four Bulgarian grapevines grown under different conditions

Abstract: Four grapevine seedlings were propagated and planted both in a greenhouse and in an experimental field. Surface components of their fresh leaves were easily obtained and analysed by gas chromatography-mass spectrometry. In total, 21 surface metabolites were identified. Unlike the greenhouse samples, the field ones possessed semiochemicals and compounds contributing to their survival under environmental stress. This study shows that the leaf surface of the grapevine possesses compounds indicating the conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…The obtained results generally confirm the reported findings of several previous studies on triterpenoids occurring in grapevine leaves (Batovska et al, 2008(Batovska et al, , 2009(Batovska et al, , 2010Berli et al, 2010, Pensec et al, 2016. In the study performed on profiling of grapevine leaf cuticular waxes of eight V. vinifera cultivars from the Upper Rhine Valley (Pensec et al, 2016), additionally cycloartanol, oleanolic aldehyde as well as stigmasta-3,5-dien-7-one were found.…”
Section: Identification Of Steroids and Triterpenoids Occurring In Leaves Of Vitis Sppsupporting
confidence: 91%
See 1 more Smart Citation
“…The obtained results generally confirm the reported findings of several previous studies on triterpenoids occurring in grapevine leaves (Batovska et al, 2008(Batovska et al, , 2009(Batovska et al, , 2010Berli et al, 2010, Pensec et al, 2016. In the study performed on profiling of grapevine leaf cuticular waxes of eight V. vinifera cultivars from the Upper Rhine Valley (Pensec et al, 2016), additionally cycloartanol, oleanolic aldehyde as well as stigmasta-3,5-dien-7-one were found.…”
Section: Identification Of Steroids and Triterpenoids Occurring In Leaves Of Vitis Sppsupporting
confidence: 91%
“…Nevertheless, several authors have reported the presence of triterpenoid compounds as constituents of cuticular waxes in different varieties of Vitis spp. leaves (Batovska et al, 2008(Batovska et al, , 2009(Batovska et al, , 2010Berli et al, 2010;Özer et al, 2017;Pensec et al, 2016). A role of triterpenoids in plant defense responses to biotic and abiotic factors is suggested as the cuticular waxes are considered to be the first line of protection towards different stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Solvent extraction, using acetone, of the red variety Storgozia leaves revealed the presence of sterols, terpenes, fatty acids, esters, ketones, one furan, and a pyrimidine nucleobase thymine. 6 The solvent extraction, using chloroform, of eight V. vinifera cultivars: Chassels, Gewurztraminer, Muscat, Pinot auxerrois, Pinot gris, Pinot noir, Riesling and Sylvaner leaves, where the investigations were determined on triterpenoids, revealed the presence of β-amyrin, lupeol, taraxerol, α-tocopherol, and β-sitosterol. 8 The solvent extraction of one cultivar using acetone and eight cultivars using chloroform revealed that the common constituents of V. vinifera leaf cultivars were β-amyrin, lupeol, α-tocopherol, and β-sitosterol.…”
Section: Resultsmentioning
confidence: 99%
“…8 The solvent extraction of one cultivar using acetone and eight cultivars using chloroform revealed that the common constituents of V. vinifera leaf cultivars were β-amyrin, lupeol, α-tocopherol, and β-sitosterol. 6,8 The SC CO 2 extracts of V. vinifera leaves, collected in October, contained β-amyrin, lupeol, α-tocopherol, and β-sitosterol. 10 The applied process parameters were 30 MPa, the temperature was in the range from 40 °C to 80 °C and with CO 2 modified with 5% and 10% of either ethanol or ethyl acetate.…”
Section: Resultsmentioning
confidence: 99%
“…Batovska and co-authors [14,15], reported that the leaf surface components of four Bulgarian Vitis vinifera L. seedlings constituting mainly triterpenoids, sterols, fatty acids, esters and heterocyclic compounds. Moreover, the qualification and quantification of triterpene and sterol contents in leaves of eight grapevine species revealed variation in cholesterol, campesterol, stigmasterol, clionasterol and sitosterol in addition to pentacyclic triterpenoids of ursane-, oleanane-, lupane-and taraxerane-type skeletons content depending on the cultivar and variety of grapevine [18].…”
Section: Introductionmentioning
confidence: 99%